“Fertilización con niveles de nitrógeno, fósforo y potasio, en arroz (oryza sativa L.)linea inia bijao y variedad capirona en bellavista-San Martín” - Gonzáles Torres, Lucila (2004)
In order to determining the appropriate leve! of Nitrogen, Match and Potassium in the fertilization of rice; line (INIA-BIJAO) and the variety (Capirona); he/she was carried out this investigation work in the "I am Founded Free", located in the sector Santa Catalina, District of San Rafael Km. 86, county of Bellavista, Department of San Martín, in a floor Loamy Franco under watering to the transplant between February and July of the 2000. The experimental design of Blocks Complete randomizados was used with factorial arrangement of 2 x 4 x 4, with 3 repetitions. These studied factors were: As factor TO: Where it was considerad a line and a variety of rice, Factor B: they took into account different nitrogen levels and 1 eat Factor C: they took in bill levels of Match and Potassium. Where the line INIA-BIJAO, obtained the biggestyíeld in shell overcoming to the variety statistícally Capirona with 7 556,70 and 7 504,20 Kg/ha versus 6 546,70 and 7 492,50 Kg/ha when it was fertilizad with dose of 180 and 160 Kg of N/ha. On the other hand the averages of the factor C (P and K) they show us statistícally averages same.